Values and Configuration of Users in the Design of Software Source Code. - COUTURE, STÉPHANE (International Journal of Communication (19328036), 2017)
Based on an empirical study of two free and open source software projects, this article focuses on how choices of design within software source code are articulated with values and may favor certain categories of actors over others. After introducing the aim and approach of the study and presenting the studied projects, the article analyzes two controversies that show the articulation of values, configuration of users, and source code design. In conclusion, I argue for the importance for communication and media studies to study the use of source code and how its design may reflect values or may facilitate or constrain the agencies of certain categories of people.